(3GdLGeY aj GdTQM (B( (3TQM GdJMQjQ(B)s - (3CHh GdMSjf RjO Hf eMeOs ((3bGSe Hf SdjeGf s)
(3ChdgG (B:s
(3jHOC HcJGH GdML Hbhdg (B: (3GdML gh GdbUO s
(3BNQgG (B:s
(3hYdi GdhdO ai Pdc VQQ dCfg jHYO Yf Cgdg hYJQJg Je GdLRA GdKGdK ef SJI BNQ ef GdcJGH TQM GdJMQjQ Hef Gddg GdYdi GdbOjQ s
(3GdLRA GdKGdK ef KeGfjI CLRGAs
(3GdfSNI ebGHdI Ydi fSNI eSehYI Ydi fSNI eSehYI Ydi fSNI GdCUd GdhGQOI ef fGMjI GdOjde HGdYQGbs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3LeYs
Keywords: (3abg GdePGgH GdCNQis